2012
DOI: 10.1002/jbm.b.32828
|View full text |Cite
|
Sign up to set email alerts
|

A new radiopaque embolizing agent for the treatment of endoleaks after endovascular repair: Influence of contrast agent on chitosan thermogel properties

Abstract: A new injectable radiopaque embolizing agent has been developed, based on chitosan thermogelling properties. Different commercial contrast agents (Isovue®, Visipaque®, and Conray®) were associated with chitosan-β-glycerophosphate. Their impact on gelation kinetic, mechanical properties, radiopacity, and cytotoxicity was tested to evaluate the best candidate and its feasibility for the treatment of endoleaks after endovascular aneurysm repair (EVAR). Addition of contrast agents did not prevent gelation at body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 45 publications
(80 reference statements)
2
27
0
Order By: Relevance
“…In contrast, here, chitosan with a 94% DDA provides much better gelation properties, with reduced gelation time and a much higher gelation rate. For example, CH/βGP12/VIS20 samples prepared here with a 94% DDA gelled immediately ( t = 0 min), and had a gelation rate of 60 Pa min −1 at 37°C, as compared to 24 min and 3 Pa min −1 for the same formulation prepared with an 83% DDA chitosan . This immediate gelation and relatively rapid increase in the G ′ values (indicative of elastic properties) could be obtained even with hydrogels containing the high content of contrast agent required to achieve good radiopacity (20–30%v/v VIS) .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In contrast, here, chitosan with a 94% DDA provides much better gelation properties, with reduced gelation time and a much higher gelation rate. For example, CH/βGP12/VIS20 samples prepared here with a 94% DDA gelled immediately ( t = 0 min), and had a gelation rate of 60 Pa min −1 at 37°C, as compared to 24 min and 3 Pa min −1 for the same formulation prepared with an 83% DDA chitosan . This immediate gelation and relatively rapid increase in the G ′ values (indicative of elastic properties) could be obtained even with hydrogels containing the high content of contrast agent required to achieve good radiopacity (20–30%v/v VIS) .…”
Section: Discussionmentioning
confidence: 82%
“…This immediate gelation and relatively rapid increase in the G ′ values (indicative of elastic properties) could be obtained even with hydrogels containing the high content of contrast agent required to achieve good radiopacity (20–30%v/v VIS) . A comparison of the storage modulus after 1 week of gelation showed that the DDA did not however influence the final mechanical properties of the gel (about 1.5 kPa, in both cases) . The addition of VIS had only a small positive effect on the final mechanical properties of the gel.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is true, for example, for the embolization of blood vessels, where the gel must be resistant to blood flow (Coutu, Fatimi, Berrahmoune, Soulez, & Lerouge, 2013). Little data exists regarding the mechanical properties required to efficiently occlude blood vessels, but our work using in vitro embolization bench testing and animal experiments on other hydrogels suggests that good gel cohesion and a rapid increase of G to or above 1 kPa are minimum prerequisites for achieving these (Fatimi, Zehtabi, & Lerouge, 2015) (submitted).…”
Section: Discussionmentioning
confidence: 97%
“…The C/GP solution should form a gel quickly in order to provide good occlusion of blood flow [37]. The viscosity and compactness of the corresponding hydrogels that strictly depend on C and GP concentrations could be further critical parameters [36].…”
Section: Discussionmentioning
confidence: 99%